Measuring the Formulation of Electric Vehicle Regional Regulations in Supporting the Transportation Electrification Policy in Jakarta - Favian, Dhien; Putra, Prayogi Ramadhani (Konsultan Surya Buanan, 2025)
This research aims to review the effectiveness of the electrification policy by The Government of Jakarta. The research method used qualitative methods with a descriptive approach to provide a comprehensive explanation regarding the implementation dynamic of local regulations regarding vehicle electrification within Jakarta. Data collection was carried out by in-depth toward The Jakarta Local Council (DPRD Jakarta) along with comparative literature reviews regarding electrification policy in Los Angeles. The results of this study indicate that the electrification policy has been implemented through various policy, such as procurement of electric buses for TransJakarta. However, the electrification policy is still carried out on a small scale due to various problems, such as budget realization, vehicle specifications, to the absence of a legal basis. For this reason, a proposal and support for a Regional Regulation on vehicle electrification is being prepared by the Jakarta Regional People's Representative Council to support the electrification policy on a massive scale.